Policy Evaluation of the role of Extracurricular activities on students' Character building and Academic Excellence: A Case Study of Cairo's Schools - Yousry, Nanis (AUC Knowledge Fountain, 2022)
The Education policies have usually been given the highest priority globally. This research reflects that the Egyptian educational system currently faces a bottleneck in applying its policies due to significant budgetary constraints. This is seen in public schools, unlike international ones. The research compares and contrasts three educational systems (public, community and international) with the purpose of examining the impact of policy processes on education. This thesis aims to explore how far the existence of extracurricular activities, as a component that complements academic education, is capable of supporting students to acquire the 21st century life skills and fulfill some of the gaps. The study analyzes the role of ECAs through the lens of three different types of schools operating in Egypt: public, community and international schools. The thesis included qualitative field research of a total of 13 semi structured interviews and 4 focus groups in three different types of schools. The interviews and focus groups were conducted with school administrators, teachers, students and parents across Egyptian schools to understand perspectives, success stories and the barriers to the implementation of ECAs. The findings of this study highlight the positive relationship between ECAs and students’ character building and academic excellence. However, the findings also show the crucial impact of an enabling environment to support the successful implementation of ECAs, which can be the determining factor of its success or failure.